Rebuilding an aging nuclear weapons complex: What should the United States do, and not do? An overview. (2nd January 2019) - Rosner, Robert; Eden, Lynn
ABSTRACT: What does the United States need to do – and what could it reasonably not do – in terms of ensuring the reliability of its nuclear arsenal and reducing the huge cost currently foreseen for maintaining that reliability? Clearly, in our view, the United States could invest less in what is broadly called "nuclear modernization" and still maintain a reliable nuclear arsenal. Reducing such investments, however, would require hard decisions about the overall shape of the US arsenal and the need to continue to support some legs of the current triad of nuclear-capable airplanes and land- and sea-based missiles. The United States could for example reduce costs without compromising security by phasing out the most vulnerable leg of the triad, ground-based nuclear missiles.